Effects of Game Outcomes and Status Instability on Spectators’ Status Consumption: The Moderating Role of Implicit Team Identification - Chang, Yonghwan; Wann, Daniel L. (Frontiers in Psychology, 2022)
This study explores the interaction effects of game outcomes and status instability and the moderating role of implicit team identification on spectators’ status-seeking behavior. The current study seeks to contribute to the existing consumer behavior and spectatorship literatures by examining the counterintuitive outcomes of winner-loser effects through the application of the biosocial theory of status. In an online experiment, NFL fans’ retrospective spectating experiences were captured and manipulated. This experiment used a 2 (game outcome: victory vs. loss) × 2 (status instability: decisive vs. close) × 2 (iTeam ID: high vs. low) between-subjects design. The findings indicated that decisive victories and close losses positively influenced spectators’ future attendance as well as their intention to purchase luxury suites and merchandise featuring images of the team mascot. Conversely, decisive losses and close victories had a negative influence. Additionally, the more spectators implicitly identified with a particular team, the more they exhibited status-seeking behavior; even close victories positively influenced the outcomes. By applying a nascent theoretical approach in the field of consumer behavior (the hormonal account), our results provide fresh insight into explaining spectators’ status-seeking behavior. Also, the findings identify specific conditions in which spectators’ status-seeking behavior is enhanced, thus suggesting ways for managers to strategically allocate their resources.